Seni (dan Sastra) dalam Perkembangan Kota Living Together, Growing Apart Hidup Bersama, Makin Berpisah - Marco Kusumawijaya (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2008)
There is a hope that we need more works of art dealing with cities. Citiness has enchanted as well as confused the people in the vortex of modernization. Citiness has attacked our consciousness stronger than ever before since everything changes so quickly either in the city or outside the city, both at the national or global level. Globalization has accelerated the transmissions of not only products and services, but also images and representations, which can step across the border as they like without symmetry. The hope shows at least three things. First, there is a need for contemplating citiness which has gone deep into our contemporary consciousness. Second, there is a confession that city and city life are supposed to be productive inspirations for arts. Third, arts have an important role in crystallizing the experience and contemplation of city life. However, cities have an ever changing form. Modernization, which have brought along industrialization and urbanization, has basically changed cities since the 18th century, which continues until now. Cities in developing countries seem to always develop, and become elusive, running faster than the speed that their inhabitants can bear, and often in unpredictable moves. The urgency of contemplating citiness is getting higher, for next year, for the first time, half of the people in the world will live in cities or in a city-like conditions. The experience of city life will become the experience of future human beings.